O ensino de ciências em espaços educativos: o uso do tema das árvores emergentes, como instrumento facilitador na promoção da preservação do ecossistema amazônico - Pereira, Ana Marcia Pontes (2022)
The study of Science exposures one of the most importante steps of education of timetable of students in elementar school. For this reason, the academic environment discussions about strategies and resources to become the learning of students more profitable and it has been usual. Among the suggested possibilities, we notice the didatic sequences. This kind of content approaches if they have been aplied can make how students demonstrate more interesting and participation inside proposal activities. Concomitant to this, Science studying, is one of the most opportune themes to be debated and it explains emergent trees. It consists a very relevant subject, that it can be better used in Science teaching practicings. This kind of theme can be done in formal and non-formal teaching spaces, these environments can be used and improve experiences and perception that profit students’ learnings. This reasearch is based on theorical fundamentation and dedicated in qualitative approach and has for general aim to comprehend as long as emerging tree theme has worked in educational spaces, it facilitates the learning teaching process for students of 4 ano Elementary School about the imporatnce of preservationod Amazonic ecosystem. Firstly, we realized exploratory investigation related to emergente trees and Science teaching, then we made the documental research about the importance of trees and their presence in educational spaces. The sequence was elaborated with views to awake in students the engagement and environmental awareness necessary for the trees be protected, this way it contributes with the natural environment and consequently with the balance the Earth’s life. For its significancy, the topicof emergentes trees can be explored with greater emphasis, the non-formal spaces and the local ideas for this approach has been done with great success in cornfield of Science teaching, it can be joined between the theory and practicing. Therefore, this research sought to provide subsidy theorists that They contribute to the learning teaching processo f Science through of the emergentes trees in educational spaces and its importance to the environmental preservation. Key-words: Emergent trees. Science teaching. Environment preservation. Educational spaces.